Open Innovation - Latouche, Pascal (Wiley-ISTE, 2020)
The purpose of this book is to explicitly describe the daily interactions that need to be implemented to transform these One To One, or One to Many, interactions into tangible (business partnerships) and intangible (relationship satisfaction) value. Through my experience, I will try to give an account of the words and behaviour of the crossed protagonists during all these years. My observations will allow to fully understand the perspectives that everyone gives themselves in interactions, in order to better understand the perceptions that result from them. It is the reality of the interactions themselves that will be exposed in order to know how to make the most of them.